Greek Economic Reforms as a Response to the Global Financial Crisis 2007-2008 - Galanidisová, Petra (2025)
This thesis examines the economic reforms implemented by Greece in response to the global financial crisis of 2007–2008. It focuses on the issues that made the Greek economy vulnerable even before the crisis, such as high public debt and structural inefficiencies. The thesis follows the key reforms adopted under three bailout programs supported by the European Union, the European Central Bank, and the International Monetary Fund. It also includes an evaluation of the social impacts of these reforms on Greek society. The findings show that although the reforms helped stabilise the economy and restore investor confidence, they also came with significant social costs. Greece’s experience, therefore, provides valuable insights for economic policy-making in similar crises.